2019
DOI: 10.1016/j.drugalcdep.2018.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Higher average potency across the United States is associated with progression to first cannabis use disorder symptom

Abstract: Objective: To determine if higher potency cannabis is associated with earlier progression to regular cannabis use, daily cannabis use, and cannabis use disorder symptom onset. Methods: Data sources were the Michigan Longitudinal Study, an ongoing prospective, high-risk family study investigating the course and predictors for substance use disorders among youth beginning prior to school entry and time-parallel national average trends in delta-9tetrahydrocannabinol (i.e., psychoactive compound in cannabis). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
43
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 27 publications
(27 reference statements)
0
43
1
1
Order By: Relevance
“…Such undesirable adverse effects may lead to a perception of treatment failure in patients who have already failed traditional pain management therapies, while dependence may potentiate the long-term use of high potency cannabis. The prolonged use of high potency cannabis increases the risk for psychotic disorders by 5-fold in daily users compared to never users [34], increases the risk of memory impairment and paranoia [35][36][37], and is associated with cannabis admissions to drug treatment [38]. People who use cannabis for medicinal purposes have more frequently reported daily or almost daily cannabis use, Fig 6. Percent of THC (A) and percent CBD (B) in CO and WA medicinal and recreational programs.…”
Section: Discussionmentioning
confidence: 99%
“…Such undesirable adverse effects may lead to a perception of treatment failure in patients who have already failed traditional pain management therapies, while dependence may potentiate the long-term use of high potency cannabis. The prolonged use of high potency cannabis increases the risk for psychotic disorders by 5-fold in daily users compared to never users [34], increases the risk of memory impairment and paranoia [35][36][37], and is associated with cannabis admissions to drug treatment [38]. People who use cannabis for medicinal purposes have more frequently reported daily or almost daily cannabis use, Fig 6. Percent of THC (A) and percent CBD (B) in CO and WA medicinal and recreational programs.…”
Section: Discussionmentioning
confidence: 99%
“…24,25,27 Previously, Hasin et al reported that the prevalence of cannabis use has doubled from 4.5% to 9.5% in the last decade in adults in the United States and overall 30% of these cannabis users advance further and develop cannabis use disorder. 27,28 Charilau et al studied the NIS database and found a threefold increase in the prevalence of cannabis use in the hospitalized US population in the last decade. 25 We observed that this increase in prevalence of cannabis use was more substantial in CVS patients.…”
Section: Discussionmentioning
confidence: 99%
“…bong) or vaporisers (electronic devices which heat cannabis into a vapour for inhalation; Russell et al ., 2018) which may influence the pharmacokinetics and transient effects of THC (Spindle et al ., 2018). Evidence suggests that among these products, those with higher THC concentrations confer the greatest harms, including increased severity of dependence (Freeman and Winstock, 2015), cannabis use disorder symptom onset and treatment (Freeman et al ., 2018 b ; Arterberry et al ., 2019) and a greater risk of, and relapse to psychosis (Di Forti et al ., 2015; Schoeler et al ., 2016; Di Forti et al ., 2019). However, few studies have explored the risk of harms carried by the more novel products becoming increasingly prevalent.…”
Section: Introductionmentioning
confidence: 99%